Optimization of a staggered pin-fin for a radial heat sink under free convection. (August 2015) - Park, Seung-Jae; Jang, Daeseok; Yook, Se-Jin; Lee, Kwan-Soo
Abstract: The design of a staggered pin-fin radial heat sink was optimized for light-emitting diode (LED) device cooling. A numerical model for various pin-fin array heat sinks was developed and verified experimentally. The design variables were determined from sensitivity analysis. Multidisciplinary optimization was conducted based on the heat sink thermal resistance and mass, using an evolutionary algorithm. From the analysis results, the staggered pin-fin radial heat sink was identified as the optimal configuration, demonstrating improved thermal performance by up to 10% while maintaining the same mass or reducing the mass by up to 12% for a given thermal resistance.